KURVA PERTUMBUHAN ANAK SEHAT USIA 3-18 BULAN DARI KELUARGA EKONOMI MENENGAH KE ATAS: Bagaimana Posisinya terhadap Standar Antropometri WHO-2005? - Abas Basuni Jahari; Jajah K. Husaini (PERSATUAN AHLI GIZI INDONESIA, 2008)
GROWTH CURVE OF HEALTHY CHILDREN 3-18 MONTHS OF AGE FROM WEALTHY FAMILIES:How Close to WHO Child Growth Standard 2005?On April 26, 2006 the WHO published a new Child Growth Standard from 0 to 60 months of age.The new child growth standard is developed based on Mulicentre Growth Reference Study(MGRS) 1997-2003 in 6 countries: Brazil, Ghana, India, Norway, Oman and the United States ofAmerica. The MGRS is unique because it was designed to develop standard based on healthychildren living in situation that provide possibility for them to grow normally according to theirgenetic potential. For this reason the WHO recommended that the new child growth standard beused as a new anthropometric reference replacing the existing NCHS-WHO growth reference. Inresponse to WHO recommendation some analyses were done to confirm the suitability of the newWHO child growth standard with local situation. One of the analyses is presented in this paper.The main objective of the analysis is to identify the position of growth curve of healthy Indonesianchildren 3-18 months of age relative to the new WHO child growth standard. The specificobjectives are: to identify the position of Weight-for-Age (W/A) curve, Length or Height-for-Age (L/A or H/A) curve. This analysis is based on growth data of healthy children from Study on “TheDevelopment of Norm of Motor Milestone Achievements in Healthy and Wellnourished Children 3-18 Months of Age 2003 in Bandung, Bogor, Malang and Surabaya (Yayah K.H, Abas B.J., HusainiM.A. et.al.)”. Children characteristics are having normal Length-for-Age, normal Weight-for-Age,and normal Weight-for-Length according to NCHS Anthropometric Reference, not suffering fromchronic diseases, not sick in the previous month, have permanent housing in good sanitation,ventilation, clean water, good toilet, etc., not twin and have normal birth-weight, their parents havegood job, and their families have no constraint in health care and economic condition. A number of1155 boys and 1097 girls were included in the analysis. The children weights and lengths wereconverted into Z_Scores using New WHO Growth standard. The sample median and standarddeviation of the Z_Score values were generated and plotted against median and standarddeviation of New WHO standard. In general the Growth Curve of Healthy Indonesian Childrenfrom mid-upper economic status families fits better in WHO Curve for both sexes, particularly atyounger ages (9 Months) in the Median Length-for-age and Weight-for-age, girls fit better thanboys in both Median length-for-age and weight-for-age, boys and girls curves fit better in medianZ_Score Weight-for-Length.Keywords: growth curve, anthropometric standard, WHO standard